Conceptual Apprenticeship – Heuristic Simplification in Training Planning Students in Negotiation and Argumentatio - Törnqvist, Anders (AESOP, 2010)
Educational experiments 2003-2009 at the Swedish School of Planning, Blekinge Institute of Technology, have tested software and other tools in training students to acquire professional skills in negotiation and argumentation. Results indicate that conceptual models, simplified, yet reflecting professional practice, facilitate learning. They do so by organising student efforts to acquire complex skills, providing immediate feedback and help to interpret teachers‟ hints and corrections. Simple models stimulate student elaboration. Complex models may need simplification and modification of target skills. In both cases improvement of learning outcomes can be observed. Software helps in externalising professional methods, visualising outcomes, and diagnosing student errors. Software also presents operating difficulties and may lead to cognitive overload for some students. Contrary to common opinion in the field, results indicate that one should assume no clear relation between features of different software and learning outcomes. Educational contexts are unavoidably different, which makes comparisons difficult. Modifying conceptual models and target skills, improving learning outcomes, should be seen rather as examples of heuristic simplification and conceptual clarification, supporting conceptual apprenticeship. This can be developed and reliably tested in a specific educational context.
Book of proceedings: Annual AESOP Congress, 2010 Space is Luxury, Aalto, July 7-10th
Keywords: Conceptual apprenticeship; heuristic simplification; negotiation; argumentation